A FTH1 gene:pseudogene:microRNA network regulates tumorigenesis in prostate cancer. Issue 4 (12th December 2017) - Chan, Jia Jia; Kwok, Zhi Hao; Chew, Xiao Hong; Zhang, Bin; Liu, Chao; Soong, Tuck Wah; Yang, Henry; Tay, Yvonne
Abstract: Non-coding RNAs play a vital role in diverse cellular processes. Pseudogenes, which are non-coding homologs of protein-coding genes, were once considered non-functional evolutional relics. However, recent studies have shown that pseudogene transcripts can regulate their parental transcripts by sequestering shared microRNAs (miRNAs), thus acting as competing endogenous RNAs (ceRNAs). In this study, we utilize an unbiased screen to identify the ferritin heavy chain 1 (FTH1) transcript and multiple FTH1 pseudogenes as targets of several oncogenic miRNAs in prostate cancer (PCa). We characterize the critical role of this FTH1 gene:pseudogene:miRNA network in regulating tumorigenesis in PCa, whereby oncogenic miRNAs downregulate the expression of FTH1 and its pseudogenes to drive oncogenesis. We further show that impairing miRNA binding and subsequent ceRNA crosstalk completely rescues the slow growth phenotype in vitro and in vivo . Our results also demonstrate the reciprocal regulation between the pseudogenes and intracellular iron levels, which are crucial for multiple physiological and pathophysiological processes. In summary, we describe an extensive gene:pseudogene network comprising multiple miRNAs and multiple pseudogenes derived from a single parental gene. The network could be regulated through multiple mechanisms to modulate iron storage in various signaling pathways, the deregulation of which results in PCa development and progression.